Second language research : methodology and design - Mackey, Alison; Gass, Susan M. (2021)
"Second Language Research: Methodology and Design is a clear, comprehensive overview of cure issues in L2 research. Authored by well-known scholars in SLA and supported by a wealth of examples from actual studies and extensive pedagogical resources, this book first introduces students to the key topics and debates in L2 research. It then guides readers step-by step through the research process - from basic principles and collection methods through study design, and reporting - to the point of being able to conduct their own research from beginning to end. This book is an essential text for students and novice researchers of SLA, applied linguistics, and second and foreign language teaching. Key Features: a wealth of graphics, visuals and exercises in each chapter. "Time to think" and "Time to do" boxes within chapters ; helpful glossary and extensive author and subject indices New to This Edition: Substantially reorganized chapters; significantly expanded chapters on qualitative and mixed methods ; Substantive revised material on computer/technology-based research ; discusses a variety of new software packages and databases, including video-mediated technology and games; discusses the Open Science Movement ; expanded coverage of corpora, processing, and psycholinguistics-based research; updated references throughout"--
Includes bibliographical references and index.
Keywords: Second language acquisition; Second language acquisition -- Research -- Methodology